The Impact of Transformational Leadership Training on Manager's Affective Commitment at PT.X - Jaya, Muh Trisna Ami; Fitriana, Nina (MOTIVA: JURNAL PSIKOLOGI, 2025)
A manager plays a crucial role in translating organizational strategies into actionable measures at the departmental level. However, low levels of affective commitment among managers may hinder organizational progress. This study aims to examine the impact of transformational leadership training on enhancing the affective organizational commitment of managers at PT. X The training was designed to strengthen managers' psychological attachment to the organization by fostering greater alignment with organizational values and enhancing leadership capacities. A quasi-experimental design with a one-group pretest-posttest approach was employed. The participants consisted of seven department managers who underwent transformational leadership training. The training was structured based on the four dimensions of transformational leadership proposed by Bass and Avolio, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The level of affective organizational commitment was measured before and after the intervention using a validated affective commitment scale. The paired sample t-test results indicated an increase in posttest scores (M = 75.5) compared to pretest scores (M = 56), with a mean difference of 19.57 and a significance level of p = 0.000 (p ≤ 0.001). These findings demonstrate that transformational leadership training significantly strengthens managers' emotional attachment to the organization. The results support the effectiveness of transformational leadership development programs, particularly within the hospitality industry, where emotional engagement plays a strategic role in enhancing service quality and employee retention.